PENGGUNAAN METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PEMBAGIAN WILAYAH WAKTU DI INDONESIA - Inayah, Atikah Nurul; Aeni, Ani Nur; Kurnia, Dadang (Jurnal Pena Ilmiah, 2017)
According to the research at fifth grade students in SDN Merapi for Social subject about Time Zone Divining in Indonesia that hasn’t run maximum. The researcher tired to solve the problem by using Class Act Research with inquiry methode. The method plan can fixing the students learning process and the result. Based on the results that have been obtained from the implementation of action found fact that is for learning planning activities and implementation activity of teacher performance in 3rd cycle is 100%. Student activitiy and result learning also have been improved. The student activity at 3rd cycle is 97,7%, the result obtained exceeded the expected target of 88%. The result learning has been increased in 3rd cycle is 97,5%. The result has reached the target is 86%. Thus, it can be concluded that the application of inquiry methodes can improve students’ result learning.